Perceptual choice boosts network stability: effect of neuromodulation?. Issue 7 (July 2015) - Warren, Christopher M.; Nieuwenhuis, Sander; Donner, Tobias H.
Abstract : A recent paper demonstrates that conscious perceptual decisions are characterized by a hallmark of attractor states in recurrent cortical networks: increased stability of cortex-wide activity patterns. We propose that this global cortical state change may be caused by a transient gain modulation through ascending brainstem systems.